2014
DOI: 10.3171/2013.10.jns131596
|View full text |Cite
|
Sign up to set email alerts
|

Impact of target location on the response of trigeminal neuralgia to stereotactic radiosurgery

Abstract: Object The authors evaluate the impact of target location on the rate of pain relief (PR) in patients with intractable trigeminal neuralgia (TN) undergoing stereotactic radiosurgery (SRS). Methods The authors conducted a retrospective review of 99 patients with idiopathic TN who were identified from a prospectively maintained database and were treated with SRS targeting the dorsal root entry zone with a maximum dose of 80 Gy. Targeting of the more proximal portion of a trigeminal nerve with the 50% isodose li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 27 publications
7
32
0
4
Order By: Relevance
“…8 Also, a target placed close to the brainstem at the level of the root entry zone 26 seems to be associated with a higher risk of numbness and higher risk of bothersome hypesthesia. This fact is confirmed by the recent paper by Sheehan et al 42 who found more numbness in a group of patients where the target used was the so-called dorsal root entry zone in comparison with the more anterior cisternal target that the authors used later on in their series. The major impact of these technical nuances may explain the large variability in the safety and efficacy reported in the literature.…”
Section: Discussionsupporting
confidence: 78%
“…8 Also, a target placed close to the brainstem at the level of the root entry zone 26 seems to be associated with a higher risk of numbness and higher risk of bothersome hypesthesia. This fact is confirmed by the recent paper by Sheehan et al 42 who found more numbness in a group of patients where the target used was the so-called dorsal root entry zone in comparison with the more anterior cisternal target that the authors used later on in their series. The major impact of these technical nuances may explain the large variability in the safety and efficacy reported in the literature.…”
Section: Discussionsupporting
confidence: 78%
“…In a recent study, the radiosurgical target appeared to affect the duration of pain relief with the target closer to the brainstem, providing extended pain relief. However, the proximal radiosurgical target was also associated with an increased risk of mild to moderate facial numbness 123. Alternative targets include the trigeminal nuclei in the brainstem or the centromedian nucleus of the thalamus 124.…”
Section: Advances In Surgical Therapymentioning
confidence: 99%
“…5,16,28 The belief behind targeting the root entry zone is that this area involves a transition zone in the axons from peripheral to central myelin, which in theory is believed to be more susceptible to radiation. 33 Several articles have documented histopathological evidence of axonal degeneration and fibrosis after GKRS.…”
Section: Discussionmentioning
confidence: 99%
“…During the patient's 5-, 113-, and 36-month pain-free durations after each GKRS, his Barrow Neurological Institute (BNI) Facial Hypesthesia Scale score was never above II, as he had mild facial numbness that was not bothersome. 33 A table describing both the latency until pain relief after each surgical and GKRS procedure, as well as the duration of pain relief achieved for each of these procedures, can be seen in Table 1.…”
Section: Third Gkrs and Postoperative Coursementioning
confidence: 99%